The Concept of Recitation (Hafazan) and Rational in Teaching and Learning in Western and Islamic Perspective - Wan Ahsani Fadhilah bt Wan Mahmud Khairi; Muhamad Faisal Ashaari (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Islamic world was once well known for its prominence of the sciences which caused by the combination between rational and recitation (hafazan) dimension in Islamic studies. This combination has brought a dynamic and rapid progress in Islamic studies in facing life challenges at that time. It reached its glorious triumph between 750 to 1258 AD. However, this field has received many criticisms with scoff and hope to get back the glorious era. This paper will talk about the important ideas inside the criticism and bring the discussion to the concept of recitation and rational thought dimension through Islamic and Western perspective. It will explain the principal element towards recitation and rational from Islamic and Western perspective as well. Qualitative study with analytical and thematic approach becomes the principle of the convincing scientific conclusion. The result has brought the fact that there are clear distinctions between these two perspectives, especially when it is seen from metaphysical side that Western party doesn’t hold the metaphysical as the matter of their principle while Islamic perspective make belief and spiritual aspects as their principle for the recitation and rational thought dimension. Keywords: recitation, civilization, education, belief